The Population, Medicinal Potential, And Chemical Properties of the Field Blewit (Blue Stalk Mushroom) Lepista Personata (Fr.) Cooke: Life Sciences-Chemical - Dunaev, Alexandr V.; Dunaeva, Elena N.; Tokhtar, Valeriy K.; Zelenkova, Viktoriya N.; Petrunova, Tatiana V. (International Journal of Life Science and Pharma Research, 2022)
This study aims to describe the population of the field blewit (blue stalk mushroom) Lepista personata (Fr.) Cooke (= L. saeva (Fr.) P.D. Orton) on the territory of the botanical Garden of the Belgorod University as a model object for studying the territorial populations of the same and other species similar in bioecology. Eating it as long as the mushroom is cooked well should not cause any kind of illness. But if consumed raw, it may cause stomach upset, pain or diarrhea in the consumer. The main health advantage of the blewit is nutritional, however, it is considered by some to hold medicinal potential. It is traditionally utilized to prevent symptoms of thiamine deficiency(beriberi) and also in wound care. This work aimed to describe the population, medicinal potential, and chemical properties of Lepista personata (Fr.) Cooke (Tricholomataceae) on the grounds of the botanical garden of Belgorod University as a model facility for the study of territorial populations of the same and other, similar in bioecology, species. The object of research was the population education L. personata on the territory of the botanical garden of Belgorod University (NIU "BelSU"). The work used methods of mycofloristics and mycocenology. The population of L. personata was studied during the fungus’s fruit-bearing period during the seasons 2012–2019. Intrapopulation structures were detected and outlined based on observations of fruit body clusters, configuration of clusters and their allocation. As a result of the research carried out on the territory of the botanical garden, 9 loci of L. personata have been identified and described. Of these, 2 loci represent elementary L. personata mycocells, 2 loci represent isolated mycocells, 4 loci represent an interconnected grouping of mycocells contacting at the propagule (propagu lum) level; a complex L. personata mycocell represents 1 locus.